Imaging-Based Deep Graph Neural Networks for Survival Analysis in Early Stage Lung Cancer Using CT: A Multicenter Study - Lian, Jie; Long, Yonghao; Huang, Fan; Ng, Kei Shing; Lee, Faith M. Y.; Lam, David C. L.; Fang, Benjamin X. L.; Dou, Qi; Vardhanabhuti, Varut (Frontiers in Oncology, 2022)
Background: Lung cancer is the leading cause of cancer-related mortality, and accurate prediction of patient survival can aid treatment planning and potentially improve outcomes. In this study, we proposed an automated system capable of lung segmentation and survival prediction using graph convolution neural network (GCN) with CT data in non-small cell lung cancer (NSCLC) patients. Methods: In this retrospective study, we segmented ten parts of the lungs CT images and built individual lung graphs as inputs to train a GCN model to predict 5-year overall survival. A Cox proportional-hazard model, a set of machine learning (ML) models, a convolutional neural network based on tumor (Tumor-CNN) and the current TNM staging system were used as comparison. Findings: A total of 1705 patients (main cohort) and 125 patients (external validation cohort) with lung cancer (stage I and II) were included. The GCN model was significantly predictive of 5-year overall survival with an AUC of 0.732 (P <0.0001). The model stratified patients into low and high-risk groups which were associated with overall survival (HR = 5.41; 95% CI, 2.32-10.14; P<0.0001). On external validation dataset, our GCN model achieved the AUC score of 0.678 (95% CI, 0.564-0.792; P < 0.0001). Interpretation: The proposed GCN model outperformed all ML, Tumor-CNN and TNM staging models. This study demonstrated the value of utilizing medical imaging graph structure data, resulting in a robust and effective model for the prediction of survival in early-stage lung cancer.